Implementasi Taman Baca Masyarakat (TBM) sebagai Agen Pemberdayaan Masyarakat - Aswari, Redi; Putra, Rona (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Community empowerment is a strategic process aimed at enhancing social, economic, cultural, and intellectual capacities through the optimization of local potential and inclusive participation in development. Community Reading Gardens (Taman Baca Masyarakat/TBM) are community-based literacy institutions that provide access to learning resources while functioning as agents of social transformation. This study examines the implementation of community empowerment initiatives conducted by TBM Tasik Malaya in Tasik Malaya Village, Curup Utara District, Rejang Lebong Regency. Using a qualitative approach, data were collected through observation and in-depth interviews with TBM managers and community members who directly benefit from the programs. Informants were selected using purposive sampling based on their involvement and knowledge of TBM activities. Data were analyzed descriptively through categorization and interpretation. The results show that TBM Tasik Malaya contributes to community empowerment through three core roles: (1) enhancing knowledge via reading services and the “Komunitas Literasi Kita Indonesia” program; (2) improving skills through creative workshops and cultural preservation initiatives such as arts and language training; and (3) providing broader opportunities by facilitating access to information, supporting the promotion of local products, and offering community health services through stakeholder collaboration. Overall, TBM Tasik Malaya functions as a multidimensional empowerment center that fosters self-reliance, cultural sustainability, and improved community welfare, making it a promising model for rural development with limited access to educational services.